(untitled) (UNED Research Journal, 2018)
The status of two economically important tree species, Huberodendron patinoi and Hymenaea oblongifolia, in Chocó, Colombia, was unknown. We used 50x50m plots to survey seedlings and trees. We found 19 adult H. oblongifolia; and 19 adults and 66 seedlings of H. patinoi (i.e. 4 Ind/ha and 33 Ind/ha, respectively). Management action is needed to increase the density of both species.